Fine needle cytology-diagnostic tool for palpable orbital and eyelid lesions - Rastogi, Nupur; Gupta, A.; Gupta, A. (International Journal of Research in Medical Sciences, 2017)
Background: Fine needle aspiration cytology in orbital lesions gained importance in the last 3 decades. FNAC can be used for aiding the clinician to plan treatment of orbital and eyelid tumors study was undertaken to evaluate the role of FNAC as a diagnostic tool for diagnosis and management of various orbital and eyelid lesions, as it is of great value in the diagnosis of new primary, recurrent and metastatic orbital tumors. Methods: Patients of different age groups presenting with orbital and eyelid lesions were studied over a period of 4 years from March 2013 to Feb 2017. The 75 patients selected for this study were clinically evaluated and then investigated with computed tomograpghy (CT) scanning. Each patient was subjected to FNAC under direct vision/ultrasongraphy guidance with sterile 22 guage needle without anaesthesia. Biopsy was done to confirm the cytological diagnosis. Results: The age of patients varied from 3 years to 70 years. On cytology 61 cases were benign and 14 malignant. Histopathological examination of 53 cases was done which confirmed the cytological diagnosis. Conclusions: FNAC is a useful, rapid, safe and cost effective method for diagnosing orbital and eyelid pathology.